2005
DOI: 10.1111/j.1467-7687.2005.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Forming a stable memory representation in the first year of life: why imitation is more than child's play

Abstract: Although 9-month-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 59 publications
1
42
0
2
Order By: Relevance
“…Most studies on imitation have looked at infants' abilities to copy relatively simple actions. Only a relatively small number of studies, such as those of Carver and Bauer (2001), Lechuga, Marcos-Ruiz, and Bauer (2001), and Lukowski et al (2005), have extended to actions that involve a series of steps. The current study is one of the first to investigate young children's imitation in more complex, hierarchically structured tasks that children become able to copy during the preschool years.…”
Section: Introductionmentioning
confidence: 98%
“…Most studies on imitation have looked at infants' abilities to copy relatively simple actions. Only a relatively small number of studies, such as those of Carver and Bauer (2001), Lechuga, Marcos-Ruiz, and Bauer (2001), and Lukowski et al (2005), have extended to actions that involve a series of steps. The current study is one of the first to investigate young children's imitation in more complex, hierarchically structured tasks that children become able to copy during the preschool years.…”
Section: Introductionmentioning
confidence: 98%
“…Findings indicating that language provided at encoding did not facilitate delayed recall are somewhat surprising given recent work documenting the effects of encoding manipulations on recall memory in infancy and early childhood. For example, previous research has revealed that allowing children the opportunity for repeated exposures to to-be-remembered information facilitates delayed recall (Bauer, Wiebe, Waters, & Bangston, 2001); other manipulations indicate that permitting immediate imitation before the imposition of a 1-month delay (Bauer, Güler, Starr, & Pathman, 2011;Lukowski et al, 2005) and training children to criterion (Bauer et al, 2011) enhances delayed recall relative to when infants only watch the sequence demonstration. One goal of the present study was to further disentangle the contribution of adult-provided supportive language at encoding and adultprovided supportive language at test using a within-subjects design in children tested at 16 months.…”
mentioning
confidence: 96%
“…By nine months, nearly half of infants can remember sequences of events after a five-week delay (Carver & Bauer, 1999). Additionally, those infants who were allowed to mimic the behaviors they observed showed better recognition of those behaviors a month later (Lukowski et al, 2005). The effect of mimicry on long-term memory was also verified at 15 months (Bauer, Hertsgaard, & Wewerka, 1995), supporting the role of mimicry in learning.…”
Section: Presence Of Observable Behaviorssupporting
confidence: 50%